Staging personhood costuming in early Qing drama - Wang, Guojun 1982- (Columbia University Press, 2020)
"Throughout Chinese history, almost all the "conquest" dynasties forced Chinese people to conform to the rulers' ethnic clothing and hairstyle in the wake of the conquests. This was no different in the early Qing period, when Manchu rulers forced their style on the Han majority. However, the theater was one of the only areas of life that was not permeated by Manchu culture and where Han costumes remained. In Exile to the Stage: Costuming and Personhood in Early Qing Drama, Guojun Wang explores clothing and costumes as indices of ethnic and gender identities during the Ming-Qing transition"--
Revision of author's thesis (doctoral) -- Vanderbilt University (2015)
Keywords: Geschichte 1650-1700; Ethnische Identität; Theaterkostüm; China; Chinese drama / Qing dynasty, 1644-1912 / History and criticism; Clothing and dress in literature; Theater / China / History / 17th century; Theater and society / China / 17th century; Costume / China / History / Ming-Qing dynasties, 1368-1912; Clothing and dress / China / History / Ming-Qing dynasties, 1368-1912; Chinese drama; Clothing and dress / Ming-Qing dynasties; Costume / Ming-Qing dynasties; Qing Dynasty (China); Theater; Theater and society; 1368-1912; Criticism, interpretation, etc; History; Hochschulschrift